Epigenetic reprogramming converts human Wharton's jelly mesenchymal stem cells into functional cardiomyocytes by differential regulation of Wnt mediators - Bhuvanalakshmi, G.; Arfuso, Frank; Kumar, Alam Prem; Dharmarajan, Arunasalam; Warrier, Sudha (BIOMED CENTRAL LTD, 2017)
BACKGROUND: Lineage commitment of mesenchymal stem cells (MSCs) to cardiac differentiation is controlled by transcription factors that are regulated by epigenetic events, mainly histone deacetylation and promoter DNA methylation. Here, we studied the differentiation of human Wharton's jelly MSCs (WJMSCs) into the cardiomyocyte lineage via epigenetic manipulations. METHODS: We introduced these changes using inhibitors of DNA methyl transferase and histone deacetylase, DC301, DC302, and DC303, in various combinations. We characterized for cardiogenic differentiation by assessing the expression of cardiac-specific markers by immunolocalization, quantitative RT-PCR, and flow cytometry. Cardiac functional studies were performed by FURA2AM staining and Greiss assay. The role of Wnt signaling during cardiac differentiation was analyzed by quantitative RT-PCR. In-vivo studies were performed in a doxorubicin-induced cardiotoxic mouse model by injecting cardiac progenitor cells. Promoter methylation status of the cardiac transcription factor Nkx2.5 and the Wnt antagonist, secreted frizzled-related protein 4 (sFRP4), after cardiac differentiation was studied by bisulfite sequencing. RESULTS: By induction with DC301 and DC302, WJMSCs differentiated into cardiomyocyte-like structures with an upregulation of Wnt antagonists, sFRP3 and sFRP4, and Dickkopf (Dkk)1 and Dkk3. The cardiac function enhancer, vinculin, and DDX20, a DEAD-box RNA helicase, were also upregulated in differentiated cardiomyocytes. Additionally, bisulfite sequencing revealed, for the first time in cardiogenesis, that sFRP4 is activated by promoter CpG island demethylation. In vivo, these MSC-derived cardiac progenitors could not only successfully engraft to the site of cardiac injury in mice with doxorubicin-induced cardiac injury, but also form functional cardiomyocytes and restore cardiac function. CONCLUSION: The present study unveils a link between Wnt inhibition and epigenetic modification to initiate cardiac differentiation, which could enhance the efficacy of stem cell therapy for ischemic heart disorders.